Regional challenges to land restitution and peace in Colombia: The case of the Lower Atrato (2015)
Government policies and practices of land restitution may impede Colombia's peace process. Given the rural origin of the contemporary Colombian armed conflict, peacebuilding and land restitution policies are linked. Based on a qualitative study undertaken by the author, this article analyses regional challenges to the implementation of land restitution policies in Colombia. The study site was the Lower Atrato region, in the Curbaradó and Jiguamiandó river basins. The study's thesis maintains that regional challenges to restitution relate to processes of regional state formation and an end to strife that includes at least five dimensions. First, land claimants face insecurity due to ongoing struggles among armed groups. Second, restitution has a contested nature that includes disputes among regional and national elites. Third, restitution expands ethnic-based land rights but is challenged to identify the rights' beneficiaries. Fourth, restitution relates to techniques of governmentality. Last, contradictions exist between development policies and restitution policies. Restitution during the ongoing war is largely infeasible given violent opposition to its processes, thereby increasing the risk of conflict reproduction. © Journal of Peacebuilding and Development, 2015.